(untitled) (Fiep Bulletin - online, 2013)
The International Physical Education Federation (IPEF) history in Uruguay began with Prof. Alberto Langlade when returning of the "II Linghíada" in 1949, he was appointed as IPEF Delegate for Uruguay, a position he held until 1980, when he died at 59 years of age. His career was brilliant; his books were distributed around the world and were used as textbooks in schools and institutes of physical education. He joined the course of Physical Education for teachers of Montevideo in 1941, being a student with high grades he was granted with a scholarship from the University of Chile to complete his studies at the Institute of Physical and Technical Education. When he returned to Uruguay he must rendered a rigorous oral examination in front of all teachers in the subjects of the third year for the revalidation of the Chilean title, the test was developed with great ease and brilliant skills. Thereafter, Prof. Langlade plays several roles, in the sports field was excellent player and then basketball coach, he was also physical trainer for the national team. In soccer was physical trainer of “Club Atlético Peñarol” in its glory years, including the National Soccer Team as well. Early on, he was Professor at the Higher Institute of Physical Education, as assistant to Prof. Pedro De Hegedus in the Chair of General Theory, Special and Didactics of Gymnastics. Practical Male Gymnastics as well. In 1949 he was appointed as Director of Studies at the Physical Education for Teacher Course, a position he held until 1967 when he retired. Although on several occasions he was offered with the General Director position of the Institute, but he never accept this position because he preferred to be in contact with classes and students.